Persepsi Guru Bahasa Inggris Pemula tentang Pelatihan Kemampuan Menulis melalui Lokakarya IELTS Daring Terintegrasi: The Perception of Early-Career English Teachers towards Writing Skill Training through Online Integrated IELTS Workshop - Yogi Saputra Mahmud (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
During the COVID-19 pandemic, teachers experienced a significant shift in the learning context from offline to online learning. Various studies suggest that teachers, particularly beginning teachers, experienced problems accommodating student teaching activities during online learning. Consequently, early-career teachers need to enhance their understanding and skills to maximize their role as effective teachers. Therefore, this community empowerment program aims to train early-career English teachers’ writing skills. Because of the COVID-19 pandemic, the workshop was conducted through an integrated online IELTS lesson via Zoom in six different sessions. Forty teachers from different schools in Indonesia participated in this program. The teachers perceived that they better understood general writing structure, paraphrasing introduction, writing body paragraphs, and conclusion. The teachers also stated that the program improved their comprehension of IELTS Writing and lowered writing anxiety. The teachers face difficulties in using vocabulary and developing ideas in writing. Based on the perceptual analysis, teacher educators are recommended to conduct future community programs to address the issues and offer programs for different skills tested in IELTS.